Robots and the rise of European superstar firms - Joel Stiebale; Jens Südekum; Nicole Woessner (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We study the impact of a recent digital automation technology - industrial robotics - on the distribution of sales, productivity, markups, and profits within industries. Our empirical analysis combines data on the industry-level stock of industrial robots with firms' balance sheet data for six European countries from 2004 to 2013. We find that robots disproportionally raise productivity in those firms that are already most productive to begin with. Those firms are able to increase their markups and overall profits, while they tend to decline for less profitable firms within the same industry, country and year. We also show that robots contribute to the falling aggregate labor income share through a rising concentration of industry sales in highly productive firms with low firm-specific labor shares. In sum, our paper suggests that robots boost the emergence of superstar firms within European manufacturing, and thereby shifts the functional income distribution away from wages and towards profits.
Keywords: D4; L11; O33; 330; Automation; Robots; Productivity; Markups; Labor share; Superstar firms